Lysophosphatidylcholine exerts an anti‐skin photoaging effect via heat shock protein 70 induction. (9th April 2021) - Hwang, Hyunmin; Chun, Hyeyeon; Kim, Daehyun; Shin, Munju; Kim, Yun‐Sun; In, Sohyun; Kim, Taeyoon; Kang, Nae‐Gyu
Abstract: Objective: Skin‐brightening agents prevent melanogenesis and reduce melanin production. However, a lower melanin content leads to weaker protection against sunlight. In this study, we evaluated the effect of lysophosphatidylcholine (LPC) and its commercial‐grade product, Lysofix Dry™ (LD), on heat shock protein 70 (HSP70) expression in epidermal cells and their anti‐skin photoaging effect against ultraviolet B (UVB) and blue light. Methods: The HSP70 induction was detected using ELISA. To confirm the inhibition of melanin synthesis by LPC or LD, the melanin content assay and gene expression were analyzed. Cell viability was assessed to verify whether LPC or LD prevents photo‐induced skin damage. The split‐face test was performed to confirm skin‐brightening effect of LD. Cream formulation with 2% of LD and placebo were used for 8 weeks, and skin brightness (L) was measured with chromameter (CR‐400, Konica Minolta). Results: LPC‐ and LD‐induced HSP70 expression in epidermal cells. LPC and LD effectively suppressed melanogenesis provoked by α‐MSH in B16 cells. They also inhibited the mRNA transcription of MITF and tyrosinase under blue light irradiation. LD increased the viability of B16 and HaCaT cells after UVB and blue light irradiation in vitro. The cream containing 2% LD increased ΔL by 1.7 after 8 weeks of use, whereas the placebo led to an increase of 0.7. Conclusion: LPC and LD were effective in suppressing melanogenesis and enhancing cell viability under UVB and blue light via HSP70 expression. Thus, they can be considered as potent skin‐brightening agents with protective effects against skin photoaging.